Pengaruh Kualitas Pelayanan dan Kepuasan Konsumen terhadap Loyalitas Pelanggan (Studi Kasus pada Pelanggan Go-Jek di Semarang) - Dheni Indra Setyaji; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
Go-Jek is a new start up company with a very significant development. But it has not yet been able to satisfycustomers. The fact is evident from the high consumer complaints at the company.The purpose of doing research is to know the influence of service quality on customer loyalty throughcustomer satisfaction Go-Jek in Semarang. The sample in this study amounted to 100 respondents usingpurposive sampling method. Analysis of the data in this study using a test validity, reliability, linear regressionanalysis, significance test and determination with SPSS 23. The influence of mediation evidenced by Sobelmethod and path analysis. The result of this study indicate that (a) service quality significantly influence tocustomer satisfaction. (b) Service quality significantly influence to customer loyalty. (c) Customer satisfactionsignificantly influence to customer loyalty. (d) Service quality significantly infuence to customer loyalty throughcustomer satisfaction. The suggestions for improving service quality on the dimensions of responsiveness andassurance to improve customer satisfaction and maintain customer loyalty.